Cytokine Profile in Human Peripheral Blood Mononuclear Leukocytes Exposed to Immunoadjuvant and Adjuvant-Free Vaccines Against Influenza - Kostinov, Mikhail Petrovich; Akhmatova, Nelli Kimovna; Khromova, Ekaterina Alexandrovna; Kostinova, Aristitsa Mikhailovna (Frontiers in Immunology, 2020)
Background. In the last decade, adjuvant-containing vaccines, exerting different effects on the immune system, including the production of cytokines, which are one of the most important regulatory systems of the body, are introduced into practice. Objectives. An effect of the immunoadjuvant polymer-subunit and adjuvant-free vaccines against influenza on the cytokine profile of mononuclear leukocytes in 27 healthy women was studied. Methods. The study of cytokine profile in human peripheral blood mononuclear leukocytes exposed to vaccines against influenza virus was determined by flow cytometry method (Cytomix FC-500, Beckman Coulter, USA) using the Multiplex-13 test system (Bender MedSystems, Austria). Results. It was established that all the studied vaccines leaded to somewhat increased levels of Th1/Th2/Th17/Th9/Th22 cytokines in the culture fluid of peripheral blood mononuclear leukocytes (PBML), which indicates the activation of both humoral and cellular immunity. An immunoadjuvant vaccine has been shown to be superior in activating the synthesis of Th1 (IL-12, INF-g, IL-2, IL-6, IL-1β, TNF-α) cytokines, IL-9 and IL-22, while the subunit vaccine was superior in activating the synthesis of IL-4, and split vaccine - of IL-5. Conclusions. Immunoadjuvant vaccine is superior in terms of inducing cellular immune effectors to a greater extent compared to subunit and split vaccines.